Voltage and temperature dependence of Random Telegraph Noise and their impacts on random number generator. (July 2022) - Xu, Mingtao; Chen, Bo; Jin, Qi; Tai, Lu; Zhan, Xuepeng; Chen, Jiezhi
Abstract: With the continuous decrease in device dimensions, Random Telegraph Noise (RTN) has drawn increasing attention. From the intrinsic stochastic features, RTN signal is adopted as an entropy source for true random number generator (TRNG). In this study, RTN time constants are investigated under various gate voltages and temperatures. Their impacts on the TRNG are revealed by performing the National Institute of Standards and Technology (NIST) test. It is found that the random verification is highly dependent on the maximum frequency ( f max ) of the clock signal in TRNG circuit, which shows linear dependence with the RTN time constant ( τc + τe ). Our findings may make a step towards generating truly random numbers and improving hardware or cyber security based on RTN phenomenon.